pointfree-1.1.1.3: Tool for refactoring expressions into pointfree form

Pointfree

Synopsis

pointfree :: String -> [String] Source #

>>> pointfree "I'm not a valid Haskell expression!" [] >>> pointfree "sum xs = foldr (+) 0 xs" ["sum = id (fix (const (foldr (+) 0)))","sum = fix (const (foldr (+) 0))","sum = foldr (+) 0"]

>>>

pointfree "I'm not a valid Haskell expression!"

pointfree "sum xs = foldr (+) 0 xs"

pointfree' :: String -> Maybe String Source #

>>> pointfree' "I'm not a valid Haskell expression!" Nothing >>> pointfree' "sum xs = foldr (+) 0 xs" Just "sum = foldr (+) 0"

pointfree' "I'm not a valid Haskell expression!"

pointfree' "sum xs = foldr (+) 0 xs"